The American dream revisited : ordinary people, extraordinary results - Sirak, Gary (Morgan James Publishing, 2017)
True stories that reveal why hard work and determination still count'and how the promise of America is still very much alive. The book is a collection of compelling stories from people that overcame a variety of adversities to achieve their American Dream. Featuring accounts of people facing a wide variety of challenges and coming from a wide variety of backgrounds, this book will turn skeptics into believers by way of everyday life examples. It instills inspiration and hope'reminding us that no matter the obstacles, this is still the land of opportunity.